Predicting Risky Behaviors Based on Emotional Schemas and Rumination in Adolescents - Zolfi Oshtolagh, Majid; Pirkhaefi, Alireza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to predict risky behaviors in adolescents based on emotional schemas and rumination.Methods and Materials: This applied, descriptive–correlational study was conducted among 150 male high school students in District 1 of Baharestan during the 2024–2025 academic year. Participants were selected through purposive sampling based on the population structure of the region. Data were collected using three validated instruments: the Risky Behaviors Questionnaire (Zadehmohammadi & Ahmadabadi, 2008), the Emotional Schema Scale—Second Version (Leahy, 2012), and the Rumination Response Scale (Nolen-Hoeksema & Morrow, 1991). After verifying statistical assumptions, inferential analyses were performed using Pearson correlation and simultaneous multiple regression in SPSS-27 to examine the predictive power of emotional schemas and rumination for risky behaviors.Findings: Pearson correlation results indicated significant positive relationships between risky behaviors and rumination, emotional rumination, guilt and shame, and blame, while comprehensibility showed a weak negative correlation. The simultaneous regression model was significant, F(6,143) = 27.99, p = 0.004, demonstrating that emotional schemas and rumination collectively explained 38.8% of the variance in risky behaviors (R = 0.623, R² = 0.388). Among predictors, rumination (β = 0.14, p = 0.01), guilt and shame (β = 0.08, p = 0.04), emotional rumination (β = 0.09, p = 0.05), and blame (β = 0.12, p = 0.01) had significant positive effects, while comprehensibility did not significantly predict risky behaviors (p = 0.11).Conclusion: The findings highlight the substantial role of emotional schemas and rumination in shaping adolescents’ risky behavioral tendencies, demonstrating that maladaptive emotional beliefs and repetitive negative thinking significantly contribute to engagement in harmful behaviors. Interventions targeting emotional schemas and rumination may effectively reduce risk-taking among adolescents.